Visiting Academic at Imperial College London - Onoufriou, Toula (My University, 2026)
Recognition of academic and professional profile and collaboration with Imperial College on inter-disciplinary research fields. Awarded since 2013 and recently renewed up to 2014.
Keywords: Sciences